Provably secure information hiding via short text in social networking tools. - Ren, Wei; Liu, Yuliang; Zhao, Junge
Utilizing OnLine Short Text (OLST) in social networking tools such as microblogs, instant messaging platforms, and short message service via smart phones has become a routine in daily life. OLST is appealing for personal covert communication because it can hide information in a very short carrier text, and this concealment is hard to detect due to the diversity of normal traffic. However, designing appropriate schemes confronts several challenges: they need to be provably secure, and their performance needs to maintain high efficiency and handy usability due to the short length of OLST messages. In this paper, we propose a family of customized schemes known as HiMix, HiCod, HiOpt, and HiPhs for text steganography in OLST. These schemes are evaluated in terms of their security and their performance with regard to two metrics that address the particular characteristics of OLST: hiding rate and hiding ease. All proposed schemes are proved to be at least computationally secure, and their performance in terms of hiding rate and hiding ease justifies their applicability in social networking tools that utilize OLST.
Keywords: Text steganography; Covert communication; Text recognition